Examining the corporate social responsibility orientation in developing countries: An empirical investigation of the Carroll's CSR pyramid - Ehie, Ike C. (My University, 2017)
We investigate the seminal Carroll's corporate social responsibility (CSR) hierarchy using a sample from Nigerian companies. Carroll (1991) outlined four major components of CSR in a cumulative framework with economic responsibilities at the base and philanthropic responsibilities at the top of the pyramid with the legal and ethical components in between. The relevance of Carroll's CSR pyramid in the African context has been questioned and the need for an empirical study on the appropriateness of the CSR pyramid in Africa has been called for. This study is in response to this call to empirically test the relevance of the Carroll's CSR pyramid in the sub-Saharan Africa region. The study also tests the proposition that CSR is viewed through the lens of philanthropy in Africa. The findings empirically validate Visser's (2006) proposition that the philanthropic component weighs heavier than both the legal and ethical components of the CSR pyramid. The results provide a basis for the reliance on corporate philanthropy and guide CSR managers in sub-Saharan Africa in understanding the orientation that would lead to a more effective CSR implementation. Copyright © 2016 Inderscience Enterprises Ltd.
Citation: Ehie, I. C. (2016). Examining the corporate social responsibility orientation in developing countries: An empirical investigation of the Carroll's CSR pyramid. International Journal of Business Governance and Ethics, 11(1), 1-20. doi:10.1504/IJBGE.2016.076337
Keywords: Corporate Philanthropy; Csr Orientation; Csr Pyramid; Developing Country; Ssa; Sub-Saharan Africa